"(x-4y-9)dx+(4x+y-2)dy=0"
Find the solution of system equation
"\\left\\{\\begin{matrix}\n x-4y=9 \\\\\n 4x+y=2\n\\end{matrix}\\right.\\\\\n\\left\\{\\begin{matrix}\n x=1 \\\\\n y=-2\n\\end{matrix}\\right."
Make a replacement
"\\left\\{\\begin{matrix}\n x=t+1 \\\\\n y=z(t)-2\n\\end{matrix}\\right."
and input in equation
"z'=-\\frac{t+1-4(z-2)-9}{4(t+1)+z-2-2}\\\\\nz'=-\\frac{t-4z}{4t+z}"
Make a replacement
"z=t\\cdot u(t)\\\\\ntu'+u=-\\frac{t-4tu}{4t+tu}\\\\\ntu'=\\frac{4u-1}{u+4}-u\\\\\ntu'=\\frac{-u^2-1}{u+4}\\\\\n\\frac{u+4}{u^2+1}du=-\\frac{dt}{t}\\\\\n\\int{\\frac{u}{u^2+1}+\\frac{4}{u^2+1}}du=-\\int\\frac{dt}{t}\\\\\n\\frac{1}{2}\\ln|u^2+1|+4\\arctan u=-\\ln|t|+\\ln|C|\\\\\n\\sqrt{u^2+1}\\cdot e^{4\\arctan u}=\\frac{C}{t}"
Then general solution is
"\\sqrt{(\\frac{y+2}{x-1})^2+1}\\cdot e^{4\\arctan \\frac{y+2}{x-1}}=\\frac{C}{x-1}"
Comments
Leave a comment